Monitoring of Antimicrobial Resistance to Aminoglycosides and Macrolides in Campylobacter coli and Campylobacter jejuni From Healthy Livestock in Spain (2002–2018) - Lopez-Chavarrias, Vicente; Ugarte-Ruiz, Maria; Barcena, Carmen; Olarra, Adolfo; Garcia, Maria; Saez, Jose Luis; de Frutos, Cristina; Serrano, Tania; Perez, Iratxe; Moreno, Miguel Angel; Dominguez, Lucas; Alvarez, Julio (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) in Campylobacter spp. (Campylobacter coli and Campylobacter jejuni) is a concern due to its importance in public health, particularly when it involves aminoglycosides and macrolides, drugs of choice for treatment of human cases. Co-resistance to these two antimicrobial classes involves transfer of genetic elements and/or acquisition of mutations in different genetic loci, which can in turn spread through vertical or horizontal gene transfer (HGT) phenomena, with each route having different potential implications. This study aimed at evaluating the association between the presence of phenotypic resistance to these two antimicrobial classes in C. coli and C. jejuni recovered from livestock at slaughterhouses in Spain (as part of the AMR surveillance program), and at assessing the genetic heterogeneity between resistant and susceptible isolates by analysing the “short variable region” (SVR) of the flaA gene. Over the 2002–2018 period, antimicrobial susceptibility test results from 10,965 Campylobacter isolates retrieved from fecal samples of broilers, turkeys, pigs and cattle were collected to compare the proportion of resistant isolates and the Minimum Inhibitory Concentrations (MICs) against six antimicrobials including gentamicin (GEN), streptomycin (STR), and erythromycin (ERY). AMR-associated genes were determined for a group of 51 isolates subjected to whole genome sequencing, and the flaA SVR of a subset of 168 isolates from all hosts with different resistotypes was used to build a Neighbor-Joining-based phylogenetic tree and assess the existence of groups by means of “relative synonymous codon usage” (RSCU) analysis. The proportion of antimicrobial resistant isolates to both, aminoglycosides and macrolides, varied widely for C. coli (7–91%) and less for C. jejuni (all hosts 0–11%). Across hosts, these proportions were 7–56% in poultry, 12–82% in cattle, and 22–91% in pigs for C. coli and 0–8% in poultry and 1–11% in cattle for C. jejuni. Comparison of the MIC distributions revealed significant host-specific differences only for ERY in C. jejuni (p = 0.032). A significant association in the simultaneous presentation of AMR to both antimicrobial classes was observed across hosts/bacterial species. The flaA gene analysis showed clustering of isolates sharing resistotype and to a lesser degree bacterial species and host. Several resistance markers associated with resistance to aminoglycosides and macrolides were found among the sequenced isolates. The consistent association between the simultaneous presentation of AMR to aminoglycosides and macrolides in all hosts could be due to the persistence of strains and/or resistance mechanisms in Campylobacter populations in livestock over time. Further studies based on whole genome sequencing are needed to assess the epidemiological links between hosts and bacterial strains.